Traditional white brined cheese as a delivery vehicle for probiotic bacterium Lactobacillus casei - Dabevska-Kostoska, Margita; Velickova, Elena; Kuzmanova, Slobodanka; Winkelhausen, Eleonora (Society of Chemists and Technologists of Macedonia, 2015)
The traditional white brined cow cheese was tested as a delivery vehicle for probiotic bacteria. The cheese was manufactured from pasteurized cow’s milk at an industrial scale, at the same time in three batches, each of 1000 liters milk. Two different initial concentrations of the probiotic bacterium Lactobacillus casei (3.86·107 and 5.81·107cfu g–1) were used. The cheese had relatively short period of ripening (40 days), large percentage of fat (~52% d.m.) and suitable pH values (~4.5) for the survival of probiotics. At the end of the ripening, the probiotic counts were 1.74·108and 3.72·108cfu g–1, respectively. There was no significant difference in most of the quality parameters at the p < 0.05 level between the two probiotic cheeses. Nitrogen fractions and fat content were the key components influencing the overall quality of the cheese samples. The principal component analysis of the sensory attributes demonstrated that the flavor contributed the most to the overall acceptance of all types of cheeses.